2022
DOI: 10.3389/frans.2022.834820
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Identification of Fentanyl and its Analogs by Electrochemical-Surface Enhanced Raman Spectroscopy (EC-SERS) for the Screening of Seized Drugs of Abuse

Abstract: Reliable identification of fentanyl and fentanyl analogs present in seized drug samples is imperative to the safety of first responders and laboratory personnel and informs the future analysis process and handling procedures. The electrochemical-surface enhanced Raman spectroscopy (EC-SERS) method developed in this work allows the in-situ preparation of the SERS substrate providing a rapid, efficient, and accurate approach to detect fentanyl, even at low percent by weight concentrations common in seized drugs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Ott et al recently reported on in situ electrochemical SERS analysis performed on fentanyl and analogs. 216 They were able to detect fentanyl in mixtures when the concentration was as little as 1−5%. Even though the SERS spectra of fentanyl and some of the precursors are remarkably similar, Mirsafavi et al differentiated them with a PLS-DA model.…”
Section: ■ Chemistry: Seized Drugs and Toxicologymentioning
confidence: 99%
See 1 more Smart Citation
“…Ott et al recently reported on in situ electrochemical SERS analysis performed on fentanyl and analogs. 216 They were able to detect fentanyl in mixtures when the concentration was as little as 1−5%. Even though the SERS spectra of fentanyl and some of the precursors are remarkably similar, Mirsafavi et al differentiated them with a PLS-DA model.…”
Section: ■ Chemistry: Seized Drugs and Toxicologymentioning
confidence: 99%
“…Even when it is not paired with a hand-held instrument, SERS is still an informative analytical technique. Ott et al recently reported on in situ electrochemical SERS analysis performed on fentanyl and analogs . They were able to detect fentanyl in mixtures when the concentration was as little as 1–5%.…”
Section: Chemistry: Seized Drugs and Toxicologymentioning
confidence: 99%
“…A deeper description and discussion regarding this type of system can be found in the following references (Dawei et al, 1987; Martín‐Yerga, Pérez‐Junquera, González‐García, et al, 2018). EC‐SERS has been described for fentanyl (Ott et al, 2022), cathinones (Gonzalez‐Hernandez et al, 2022), THC (Bindesri et al, 2020), and other analytes (Dendisová et al, 2019; Hernández et al, 2018; Hernandez et al, 2022; Hernandez, Perales‐rondon, Arnaiz, et al, 2020; C. Huang & Hsiao, 2020; Ibáñez et al, 2020; Martín‐Yerga, Pérez‐Junquera, Hernández‐Santos, & Fanjul‐Bolado, 2018; Velička, Adomavičiūtė, et al, 2020; Velička, Zacharovas, et al, 2020) including tip‐enhanced variations (Zaleski et al, 2016; Zeng et al, 2015).…”
Section: Overview Of Sers Theorymentioning
confidence: 99%
“…A simple and rapid EC‐SERS protocol was reported in Ott et al that allowed for sensitive and selective detection of fentanyl and several fentanyl analogs (Ott et al, 2022). In their protocol, in situ generation of the silver SERS substrate was achieved with silver screen‐printed electrodes and a perchloric acid/potassium chloride electrolyte.…”
Section: Seized Drug Analysismentioning
confidence: 99%
“…Raman spectroscopy is a valuable tool for chemical characterization and sensing, showing unique fingerprints for molecules that have Raman-active modes . The high specificity afforded by this technique along with rapid acquisition has allowed real-time sensing of many important biomolecules, drugs, hazardous materials, and more. Raman spectroscopy, while highly diagnostic, does not offer sensitivity comparable to other techniques such as nuclear magnetic resonance (NMR) spectroscopy and high-performing liquid chromatography/gas chromatography (HPLC/GC). ,, In efforts to solve this problem, researchers exploit surface-enhanced Raman scattering (SERS), a phenomenon that occurs when the technique is coupled to structures that increase electronic near fields, allowing for both high sensitivity and selectivity in sensing. Structures that afford the best SERS effect are nanoparticles supporting strong surface plasmon resonances . Utilizing plasmonic particles, detection limits for many Raman labels and analytes have been pushed far, and in some cases with extremely sophisticated setups, single-molecule detection has even been achieved. , …”
Section: Introductionmentioning
confidence: 99%